2011
DOI: 10.1371/journal.pone.0015646
|View full text |Cite
|
Sign up to set email alerts
|

Proxy Measures of Fitness Suggest Coastal Fish Farms Can Act as Population Sources and Not Ecological Traps for Wild Gadoid Fish

Abstract: BackgroundEcological traps form when artificial structures are added to natural habitats and induce mismatches between habitat preferences and fitness consequences. Their existence in terrestrial systems has been documented, yet little evidence suggests they occur in marine environments. Coastal fish farms are widespread artificial structures in coastal ecosystems and are highly attractive to wild fish.Methodology/Principal FindingsTo investigate if coastal salmon farms act as ecological traps for wild Atlanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
86
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 36 publications
3
86
1
1
Order By: Relevance
“…The WF2 shrimp had the same total FA content as shrimp from the feeding experiment (Olsen et al 2009), almost 7 mg g −1 (Table 3). Fish aggregated at a farm tend to have alterations in body condition (Dempster et al 2011, Fernandez-Jover et al 2007) and FA composition (Fernandez-Jover et al 2007, and our results indicate the same for shrimp. However, we have no knowledge on whether shrimp have ingested organic waste directly through faeces or feed pellets, or indirectly by feeding on influenced infauna that have had this diet.…”
Section: Discussionsupporting
confidence: 68%
“…The WF2 shrimp had the same total FA content as shrimp from the feeding experiment (Olsen et al 2009), almost 7 mg g −1 (Table 3). Fish aggregated at a farm tend to have alterations in body condition (Dempster et al 2011, Fernandez-Jover et al 2007) and FA composition (Fernandez-Jover et al 2007, and our results indicate the same for shrimp. However, we have no knowledge on whether shrimp have ingested organic waste directly through faeces or feed pellets, or indirectly by feeding on influenced infauna that have had this diet.…”
Section: Discussionsupporting
confidence: 68%
“…For example, an elevated abundance of pouting Trisopterus luscus has been reported around offshore wind turbines located in the southern part of the North Sea, probably due to the enhanced provision of prey species that live on the structures (Reubens et al 2011). Similarly, both saithe Pollachius virens and cod Gadus morhua are the 2 most frequently observed fish species aggregating around sea cage structures for salmon farming in coastal waters in Norway, and diet and condition data indicated that wild saithe and cod benefited from their associations with salmon farms due to access to greater amounts of food (Dempster et al 2011). However, there is little published information on the feeding habits of fish assemblages in association with the physical presence of offshore oil and gas installations in the North Sea.…”
Section: Introductionmentioning
confidence: 99%
“…The physiological consequences of this new food source on local fish populations are still unclear . A recent study has shown that farms do not seem to negatively affect wild fish species like saithe Pollachius virens and Atlantic cod Gadus morhua but rather act to enhance the body condition of farm-associated fish (Dempster et al 2011). In parallel, consumption of lost food by wild fish may buffer the environmental impact on the benthos underneath farms (e.g.…”
Section: Introductionmentioning
confidence: 99%